The Interdependence of Quality Variations, Selling Effort and Price - Brems, Hans (Quarterly Journal of Economics, 1948)
I. The problem, 418. — The assumptions, 420. — II. Diagrammatic analysis, 420. — The marginal cost curve: selling-effort and quality criteria independent, 422; selling-effort and quality criteria not independent, 431. — Different ways of increasing sales, 432. — The concept "quality improvement, " 435. — III. Varying the price assumption, 435. — The "locus, " 437. — The optimum price, 437. — IV. The problem of the initial quality, 438.